Chromosomal aberrations in Channa punctatus(Bloch) from Hussainsagar Lake, Hyderabad (A.P) - Kumari, S Anitha; Ramkumaran, Sree (Indian Journal of Fisheries, 2014)
A study was conducted to assess the cytogenetic changes in an airbreathingfish, Channa punctatus inhabiting the polluted water of Hussainsagar lake.Several structural chromosomal aberrations such as chromatid breaks and gaps,fragments, sister-chromatid exchanges, dicentric and ring type of chromosomeswere observed in these fishes in comparison to the fishes collected from othernon-polluted water bodies thus indicating induced mutation in fishes living inHussainsagar waters.